Sustaining education through a flipped learning approach - Abd Rahman, Siti Fatimah; Md Yunus, Melor; Hashim, Harwati; Ahmad, Noorlila (2023)
21st-century education makes educators constantly explore the best teaching style to improve students’ experiences and engagement in the classroom. The interest in flipped learning has risen aggressively in the past decades as this unique approach allows educators to provide more meaningful learning to students. Understanding the factors affecting Malaysian English as a Second Language (ESL) lecturers’ attitudes and intention in using flipped learning is crucial in ensuring its successful execution. Based on the Unified Theory of Technology Acceptance and Use of Technology (UTAUT), this research studied the six factors, including (1) Performance Expectancy, (2) Effort Expectancy, (3) Social Influence, (4) Facilitating Conditions, (5) Computer Self-Efficacy and (6) Computer Anxiety. A data collection instrument was developed to quantify the factors and test the hypotheses. Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) were used to analyse the data. There were 206 respondents from various universities all over Malaysia. The results indicated that the significant factors in the ESL lecturers' attitude toward flipped learning are Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Computer Self-Efficacy and Computer Anxiety. This study provides a modified model to help educators and stakeholders implement flipped learning in planning and designing phases for English as a Second Language teaching and learning purposes. Our model is registered under the intellectual property with the licence number LY2021E04255.